The seeding of ice algal blooms in Arctic pack ice: The multiyear ice seed repository hypothesis. Issue 7 (3rd July 2017) - Olsen, Lasse M.; Laney, Samuel R.; Duarte, Pedro; Kauko, Hanna M.; Fernández‐Méndez, Mar; Mundy, Christopher J.; Rösel, Anja; Meyer, Amelie; Itkin, Polona; Cohen, Lana; Peeken, Ilka; Tatarek, Agnieszka; et al.
Abstract: During the Norwegian young sea ICE expedition (N‐ICE2015) from January to June 2015 the pack ice in the Arctic Ocean north of Svalbard was studied during four drifts between 83° and 80°N. This pack ice consisted of a mix of second year, first year, and young ice. The physical properties and ice algal community composition was investigated in the three different ice types during the winter‐spring‐summer transition. Our results indicate that algae remaining in sea ice that survived the summer melt season are subsequently trapped in the upper layers of the ice column during winter and may function as an algal seed repository. Once the connectivity in the entire ice column is established, as a result of temperature‐driven increase in ice porosity during spring, algae in the upper parts of the ice are able to migrate toward the bottom and initiate the ice algal spring bloom. Furthermore, this algal repository might seed the bloom in younger ice formed in adjacent leads. This mechanism was studied in detail for the dominant ice diatom Nitzschia frigida . The proposed seeding mechanism may be compromised due to the disappearance of older ice in the anticipated regime shift toward a seasonally ice‐free Arctic Ocean. Plain Language Summary: Ice algae are important primary producers in the Arctic food web. These organisms are adapted to living under extreme conditions in the sea ice environment. It is not well known how ice algae overwinter in the Arctic and are able to bloom the following spring. During the N‐ICE campaign R/V Lance was frozen into the pack ice north of Svalbard between January and June 2015 and enabled scientists to study the sea ice and the ice algae from winter to summer. We found that multiyear ice because of its characteristic physical structure can function as a seed repository for ice algae and secure a sufficient seed stock for the spring ice algae bloom. During the last decades a change in the ice regime of the Arctic Ocean has been observed where multiyear ice is disappearing fast and ice‐free summers could be a reality within this century. This could compromise the seeding mechanism and lead to profound changes in the ice algal species composition and primary productivity. Key Points: Multiyear ice may act as a repository for ice algae during winter The repository can seed ice algal blooms in adjacent younger ice during spring A shift from a multiyear ice to a first year ice regime in the Arctic might compromise this seeding mechanism